Estimasi Biaya Pelayanan Kesehatan sebagai Upaya Pencegahan Defisit Dana Jaminan Sosial untuk Penyakit Gagal Ginjal - Mutiara Nurtandhee (BPJS Kesehatan, 2023)
Not all medical expenses were paid promptly in 2018, which resulted in a deficit for BPJS Kesehatan. If DJS cannot meet the costs of health services, it will have an impact on other people who need care. Kidney failure is one of the catastrophic diseases with the highest costs, costing up to 6.5 trillion rupiah in 2021, an increase of 190% compared to 2020. This is also due to the increase in the number of sufferers, followed by an increase in cases of kidney failure. Some of the procedures include CAPD, hemodialysis, and organ transplantation, which can cost up to hundreds of millions of rupiah per patient. This research aims to forecast the prevalence rate of kidney failure in Indonesia for 2023–2025 using the Exponential Smoothing method and the literature study method. The results showed that people aged >45 years were more likely to get kidney failure. Compared to women, the prevalence for men is higher, which serves as a warning to the community to maintain a healthy lifestyle. Following the hypothesis, the total cost of kidney failure will increase with the increase in hemodialysis patients and cases. The total cost of treatment is expected to be between 7 and 10 trillion rupiah in 2023-2025. It is known that the cost containment scheme has succeeded in overcoming the problem of cost control in several countries. The United States uses cost sharing as a cost control scheme for the treatment of ESRD (End-Stage Kidney Disease). Therefore, Indonesia can also implement a cost-sharing scheme that is based on the forecasting results of kidney failure costs. This scheme is appropriate to overcome the problem of controlling insurance costs.